Efeito agudo do exercício físico sobre o desempenho matemático, controle inibitório e variabilidade da frequência cardíaca - CORDEIRO, Felipe Barradas (2022)
43% of students around the world believe they are not good at math, and 59% of students worry because they think math classes are difficult. One of the factors that can influence mathematical performance in children is mathematics anxiety (AM), in addition mathematical anxiety has cognitive markers and effect on the autonomic nervous system. Like anxiety, cognitive responses are also related to modulations of HRV Heart Rate Variability. In this context, physical exercise has a direct impact on general anxiety, cognition, school performance, and HRV. The aim of this paper is to investigate the acute implications of physical exercise on cognitive, academic and HRV performance of children with high mathematical anxiety. METHODS: 99 elementary school students between 10 and 12 years old divided by level of mathematical anxiety (high AM = HMA; low AM = AML) and then randomized into control or exercise groups, forming 4 groups: HMA-Ex; HMA-Re; LMA- Ex and LMA- Re. All participants performed a mathematical performance test followed by a Flanker test, and after 20 minutes of moderate exercise or complete rest, this sequence was repeated. During all tests and students were being monitored by a heart monitor to analyze HRV. Comparisons were made between the moments before and after the experimental conditions for different levels of AM. RESULTS: The number of absolute performance and mean complexity attributes in mathematical performance were higher after the experimental condition only for the LMA-Ex group (p <0.05; p <0.05, respectively). The reaction time for incongruent conditions is shorter after the experimental condition for HMAEx (p <0.05), HMA-Re (p <0.05) and LMA-Ex (p <0.05) groups. The reaction time was shorter for congruent conditions after experimental conditions for HMA-Re (p <0.05) and LMA-Ex (p <0.05) groups. Conflict cost decreased after experimental condition for HMARe (p <0.05), LMA-Ex (p <0.05) and LMA-Ex (p <0.05) groups. Intra-Individual Standard Deviation decreased after the experimental condition in the LMA-Ex group (p <0.05). There was an increase in the Poincaré Plot SD2 / SD1 index in the HMA-Ex (p <0.05) and LMAEX (p <0.05) groups, as well as a decrease in the LMA-Re (p <0.05) group. . SampEn increases in the LMA-Re group (p <0.05). There was still a reduction in the LF index for the HMA-Re group (p <0.05). There was a mean increase in RR intervals for the HMA-Re (p <0.05) and LMA-Re (p <0.05) groups and the RMSSD variable for the same groups (HMARe: p <0.05; LMA -Re: p <0.05). SDNN reduces the LMA-Re group (p <0.05) and increases the HMA-Re group (p <0.05). CONCLUSION In the Mathematical Performance there was significant difference between before and after the experimental condition only for the LMAEx group. All children who exercised showed improvement in reaction time and children who rested with high anxiety also improved. In IIV, among children who were at rest, those with low anxiety improved their IIV and children with high mathematical anxiety showed no differences. For HRV, exercise decreased vagal modulation for children with high and low anxiety, however, in resting groups there was a decrease in vagal tone for children with low mathematical anxiety and sympathetic activation for children with high anxiety.